Development of Islamic Religious Education Learning Media Based on Pop-up Books on Taharah Material at SDN 95 Tanete, Maiwa District, Enrekang Regency - Sukwanty. T; Sitti Jamilah Amin; Buhaerah; Usman; Abdul Halik (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
Using appropriate learning media will make students more interactive in the teaching and learning process. One of them is realized by developing media that can improve student learning outcomes. Therefore, researchers took the initiative to develop books as a medium that can attract students' attention. With the pop up book, it is hoped that it will make it easier for students to understand difficult material. The material used is taharah material with the subject of ablution. This type of research is Research and Development, with the ADDIE development model which has 5 systematic research stages, namely analysis, design, development, implementation and evaluation. Product trials were carried out on grade 2 students at SDN 95 Tanete, Maiwa District, Enrekang Regency. Data collection instruments were used to obtain data, namely interviews, tests and questionnaires. Meanwhile, the data analysis technique uses N-Gain Score. The results of research on developing pop up books as learning media show that, 1) the media aspect obtained material verification results 1 and 2 of 80% and 85% in the valid category, the media aspect obtained verification results of 80% in the valid category and the PAI learning aspect obtained the verification results were 87.5% in the very valid category, 2) pop up books were included in the practical category for use as PAI learning media with analysis results of 80%, 3) this media was included in the effective category for use based on the results of the posttest and pretest with the calculation results N-Gain for basic competencies 3.9 and 4.9 is 0.5 and 0.7